2016
DOI: 10.1080/09637486.2016.1185771
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of heat-killedLactobacillus plantarumBF-LP284 on Meth-A tumor cells in BALB/c mice

Abstract: Probiotics exert numerous effects on human well-being. Here, heat-killed Lactobacillus plantarum BF-LP284 (H-Lp) was isolated as a potent immuno-modulator among 15 strains of lactobacilli in terms of TNF-α induction ability in peritoneal macrophages. In vitro TNF-α and IFN-γ induction in Peyer's patch (PP) cells was higher when incubated with H-Lp than with live L. plantarum BF-LP284 (L-Lp). Suppression of syngeneic Meth-A tumors in a murine model by oral administration of H-Lp was also greater than that of L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Since the manifestation of probiotics impacts on several diseases from non-viral to viral ones [ 12 , [37] , [38] , [39] , [40] , [41] ], several studies have surveyed the probiotic roles in immune responses of influenza-infected animal models. It has been fully demonstrated that upon infection with influenza, many cytokines such as IL-12 (one of the mediators of Th1 immune-response), interferon (IFN)-γ (representative of Th1 cytokine), IL-4 and IL-10 (Th2 cytokines), IL-1α, IL-1β, IL-6, and tumor necrosis factor (TNF)-α (pro-inflammatory cytokines), and IFN-α and IFN-β are produced in the respiratory tract [ 36 , [42] , [43] , [44] ].…”
Section: Immunomodulatory Role Of Probiotics On Influenza Virus In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the manifestation of probiotics impacts on several diseases from non-viral to viral ones [ 12 , [37] , [38] , [39] , [40] , [41] ], several studies have surveyed the probiotic roles in immune responses of influenza-infected animal models. It has been fully demonstrated that upon infection with influenza, many cytokines such as IL-12 (one of the mediators of Th1 immune-response), interferon (IFN)-γ (representative of Th1 cytokine), IL-4 and IL-10 (Th2 cytokines), IL-1α, IL-1β, IL-6, and tumor necrosis factor (TNF)-α (pro-inflammatory cytokines), and IFN-α and IFN-β are produced in the respiratory tract [ 36 , [42] , [43] , [44] ].…”
Section: Immunomodulatory Role Of Probiotics On Influenza Virus In Thmentioning
confidence: 99%
“…Among several genera of bacteria (and yeasts) that identified and defined as probiotics, health benefits of Lactobacillus and Bifidobacterium on the host have been proved and are generally consumed as a part of fermented foods like those in dietary supplements [ 2 ]. There are some reports about probiotics potential in promoting health benefits by regulating allergic reactions [ [3] , [4] , [5] ], protecting the hosts against bacterial and viral infection [ 1 , [6] , [7] , [8] , [9] ], and even reducing the tumor growth in some cancer models [ [10] , [11] , [12] ]. The probiotics-conferred health benefits are attributable to their effects on the immune system.…”
Section: Introduction To Probiotics General Attitudes and Functionsmentioning
confidence: 99%
“…As a result, tumour growth was suppressed and microvessel density was lowered in an IL-17 dependent manner in treated animals. Finally, the oral administration of heat-inactivated Lactobacillus plantarum BF-LP284 in mice injected with Meth A tumour cells culminated in tumour volume reduction and the modulation of cytokine production and lymphocyte populations [119].…”
Section: Beneficial Modulation Of Anti-tumour Immune Responses In Extmentioning
confidence: 99%
“…Many potential health benefits of L. plantarum have been reported, such as effects on cholesterol, diarrhea, and irritable bowel syndrome (Barreto et al, 2014). After growing in glucose or sucrose, L. plantarum strains can produce EPS (Ismail and Exopolysaccharide from Lactobacillus plantarum LRCC5310 offers protection against rotavirus-induced diarrhea and regulates inflammatory response Nampoothiri, 2010), and the reported benefits include antioxidant (Zhang et al, 2013), antitumor (Shin et al, 2016), anti-inflammatory activity (Toshimitsu et al, 2017), as well as antiviral activity against herpes simplex virus (Matsusaki et al, 2016); however, no effects against rotavirus have been reported previously.…”
Section: Introductionmentioning
confidence: 99%